Political shocks and financial markets: Regression-discontinuity evidence from national elections - Daniele Girardi (University of Massachusetts, Department of Economics, 2018)
Despite growing interest in the effect of political-institutional factors on the economy, causally identified evidence on the reaction of financial markets to electoral outcomes is still relatively scarce, due to the difficulty of isolating causal effects. This paper fills this gap: we estimate the "average treatment effect" of left-wing (as opposed to conservative) electoral victories on share prices, exchange rates, and sovereign bond yields and spreads. Using a new dataset of worldwide national (parliamentary and presidential) elections in the post-WWII period, we obtain a sample of 954 elections in which main parties/candidates can be classified on the left-right scale based on existing sources and monthly financial data are available. To achieve causal identification, we employ a dynamic regression-discontinuity design, thus focusing on close elections. We find that left-wing electoral victories cause significant and substantial short-term decreases in stock market valuations and in the US dollar value of the domestic currency, while the response of sovereign bond markets is muted. Effects at longer time horizons (6 to 12 months) are very dispersed, signaling large heterogeneity in medium-run outcomes. Stock market and exchange rate effects are stronger and more persistent in elections in which the Left's proposed economic policy is more radical, in developing economies, and in the post-1990 period.
Keywords: 330